The factors affecting business growth of Small And Medium Enterprises (SMEs): the case of Ambang Dorongan SDN. BHD. / Roslan Mohamed…[et al.] - Mohamed, Roslan; Alias, Mohd Azmil; Shahuddin, Shazmira (2014)
The study is aimed at analysing and examines the current operation of Ambang Dorongan Sdn. Bhd. (ADSB), a Bumiputera company manufacturing frozen food products and identifying issues pertaining to the growth of the company. Since ADSB are located in the rural areas, the company has managed to assist the economic development of the rural areas especially in providing job and business opportunities to the residents. However due to intense competition the company’s revenue and profit starts declining in 2009 and only posed a slight increase in 2012. The survival of ADSB is crucial as the rural economy are at risk if the company continuously facing decline in revenue and profit. The study helps to identify factors that affect the growth of the company and proposed recommendations to stimulate the company growth. The method used in this study is business model such as SWOT, PEST and Porter Five Forces analysis. Data and information were gathered through interviews, survey and secondary data such as audited account. The result shows that three main factors affecting the company’s growth are the marketing, production and the human resources management. The recommendation proposes ADSB to identify and penetrate new market locally and abroad to increase sales revenue. Efficiency in production to be achieved by introducing innovation and improvement coupled with structured training system will help ADSB to achieve high profit growth.